Ecological impacts of the industrial revolution in a lowland raised peat bog near Manchester, NW England - Sandra Garcés‐Pastor; William J. Fletcher; Peter A. Ryan (Ecology and Evolution, 2023)
Abstract (1) Ombrotrophic peat bogs provide valuable records of environmental change on long timescales but are rarely preserved near the major centers of industrial activity. Holcroft Moss is a rare example of a stratigraphically intact lowland peat bog in NW England, which provides a valuable opportunity to trace industrial impacts on vegetation in a sensitive environmental archive close to the early industrializing cities of Manchester and Liverpool. (2) We reconstructed environmental changes at Holcroft Moss before and after the Industrial Revolution using a decadal‐scale record of pollen, non‐pollen palynomorphs, microcharcoal, peat composition (organic content and ash‐free bulk density) and heavy metal content, constrained by a radiocarbon and SCP (spheroidal carbonaceous particle) chronology. We examine the relationship between abiotic and biotic environmental tracers using principal component analysis and evaluate the role of local and regional climatic and anthropogenic drivers using canonical redundancy analysis and partitioning of variation. (3) Results show significant changes in bog vegetation composition during the last 700 years. Prior to 1750 CE, climate and agro‐pastoral activity (grazing and fires) were the main drivers of vegetation change. Subsequently, regional coal‐fired industry contributed to major increases in atmospheric pollutants (dust, heavy metals, and acid deposition) that severely impacted vegetation, driving the decline of Sphagnum. Grasses rose to dominance in the 20th century associated especially with bog conversion and cumulative nitrogen deposition. Although atmospheric pollution significantly decreased in the post‐industrial era, vegetation has not returned to pre‐industrial conditions, reflecting the ongoing impact of global change drivers which pose challenges for conservation and restoration. (4) Synthesis. Paleoecological studies are needed to reveal the long‐term history of vegetation degradation and to offer guidelines for restoration and conservation practices. This study reconstructs the last 700 years of a peat bog located between Manchester and Liverpool, revealing the timing and nature of vegetation changes across the trajectory of early industrialization and eventual post‐industrial decline. Our study reveals the progressive dominance of regional anthropogenic forcing and highlights that the present‐day vegetation does not have past analogs within the last 700 years. Conservation measures favoring the reintroduction of Sphagnum are justified in redressing the major biological legacy of the Industrial Revolution, while steps to increase Calluna should also be considered in light of its resilience to dry and fire‐prone conditions.